COMPARISON OF TWO HAEMODYNAMIC MONITORING SYSTEMS IN THE CARDIAC CATHETERIZATION LABORATORY: THE MANIFOLD (MANUAL) VS. AUTOMATED ACIST CVI®. (April 2021) - Mahmud, Azra; Balghith, Mohammad; Ayoub, Kamal; Alanezi, Abdulrehman Fahad; Alanezi, Abdulrehman; Alhadadi, Bandar; Alshammary, Hanan; Alshehri, Jaber; Alshammary, Majed; Alghamdi, Ali; Khan, Fayaz Mohammad
Abstract : Objective: Hemodynamic monitoring is an integral part of any cardiac catheterization procedure and can be potentially prone to many distortions, including damping and resonance. The optimum damping ratio recommended for accurate haemodynamic monitoring ranges between 0.4 to 0.8. The most common systems used include Manifold, the manual system and the automated, ACICT CVi® device, which is claimed to be as accurate as the manual system and easier to use. The aim of this prospective study was to compare damping ratio, ascending aortic pressure waveform and invasive blood pressures (BP) between manifold and ACIST CVi®, in patients undergoing cardiac catheterization. Design and method: This study was conducted at the cardiac catheterization Laboratory at King Abdul-Aziz Cardiac Center, National Guard Health Affairs, Riyadh in adult patients undergoing elective cardiac catheterization procedures. The fast-flush test was performed at the beginning of the procedure using manifold and ACIST in a cross-over fashion. The square wave was analysed to calculate the damping coefficient for each device. Data was analyzed by JMP Pro (SAS for Windows, Version 13) p < 0.05 considered significant. The patients gave informed consent and the study was approved by the Institutional Ethics Committee. Results: We compared the two systems in a randomised cross-over fashion in 54 subjects (mean age 58.1 ± 12, 24% females). The mean damping ratio was 0.61 ± 0.11 (range 0.34–0.95) with manifold vs. 0.95 ± 0.27 (range 0.53–2.1) with ACIST, mean difference 0.33, p < 0.0001. The over-damped ACIST yielded lower BP measurements compared with manifold; mean difference 6 mm Hg systolic and 5 mm Hg diastolic with almost 30% of the subjects showing a discrepancy of > 10 mm Hg between the two systems. Conclusions: To the best of our knowledge, this is the first study comparing a manual haemdynamic monitoring system to an automated one used widely in cardiac catheterization laboratories. In our study, while the mannifold met the international recommendations for accurate haemodynamic monitoring, ACIST device was overdamped, resulting in significant underestimation of invasive pressures. We recommend using the manifold system for studies involving haemodynamically compromised patients and in patients depending upon accurate haemodynamics for diagnostic purposes.